2017
DOI: 10.1111/acem.13230
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hospital “Best Practice” Mandates on Prescription Opioid Dispensing After an Emergency Department Visit

Abstract: Objective Washington State mandated seven hospital “best practices” in July 2012, several of which may affect ED opioid prescribing and provide a policy template for addressing the opioid prescription epidemic. We tested the hypothesis that the mandates would reduce opioid dispensing after an ED visit. We further assessed for a selective effect in patients with prior risky or chronic opioid use. Methods We performed a retrospective, observational analysis of ED visits by Medicaid fee-for service beneficiarie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 31 publications
4
36
0
Order By: Relevance
“…Other studies have demonstrated that educational programs, state monitoring programs, and a "Best practices initiative" continue to be effective in reducing opioid prescribing. [16] Our findings mirrored those of Lin et al, 2017 [9] using VHA data demonstrating the increase and subsequent decrease in opioid prescribing prepost the 2013 OSI respectively.…”
Section: Opioid and Non-opioid Analgesicssupporting
confidence: 87%
“…Other studies have demonstrated that educational programs, state monitoring programs, and a "Best practices initiative" continue to be effective in reducing opioid prescribing. [16] Our findings mirrored those of Lin et al, 2017 [9] using VHA data demonstrating the increase and subsequent decrease in opioid prescribing prepost the 2013 OSI respectively.…”
Section: Opioid and Non-opioid Analgesicssupporting
confidence: 87%
“…There is a need to better understand the effectiveness of treatment guidelines, independent of other interventions, to inform future policies, care improvement efforts, and research . Moreover, the effects of general guidelines on specific ED sub populations (e.g., patients with chronic opioid use or new fracture) is not known.…”
mentioning
confidence: 99%
“…Accordingly, opioid‐sparing approaches that achieve adequate pain control in ED patients are needed. Several methods and guidelines have been proposed to decrease opioid use in ED patients . Our study demonstrates that a simple action based on the early prescription of the tramadol/acetaminophen combination was associated with a decrease in the amount of opioid prescriptions written by emergency physicians.…”
Section: Discussionmentioning
confidence: 68%